FOREIGN DIRECT INVESTMENTS IN THE REGIONS AS A FACTOR OF UZBEKISTAN’S ECONOMIC GROWTH - Akishova Shakhnoza Davletovna (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
Investing in the economy of the Republic of Uzbekistan as a whole and in its regions in particular is a task of paramount importance because the well-being of both the state itself and its citizens will depend on its proper execution. This determines the relevance of the research topic. Investments in the regions are aimed at increasing the regional product and production volumes, mastering new activities, and developing the existing material and technical base.